Democracia e política educacional no governo Lula - Germann, Paulo Roberto de Souza (2011)
The current study is a bibliographical analysis of the educational policies implemented in Brazil during the two Lula administrations with the promotion of a new relationship between the State and society through a more participative democracy. The text presents an analysis of democracy as a universal value, demonstrating how the concept has been reinterpreted in different ways today. Departing from this discussion, it went on to describe the State and democracy in Brazil as a way to contextualize Lula government and the main educational policies it put into practice. Based on documents for reference it emphasized theoretical and democratic practices by the government, taking documents by their words as they were published. The main focus of the research was on the Final Document of the National Conference on Education (CONAE) among other texts of reference of educational policies for the period. The research was framed on the reconstruction of theoretical models of democracy and its correlation with education. It started, as critical base, on the assumption that democracy as a universal value is inseparable from the commitment toward equality, freedom and political participation. Liberal, communitarian and socialist concepts of democracy were compared. The study came to the conclusion that the educational policies of the Lula government were more tuned with the communitarian interpretation, approaching it also to the liberal conception. The main references for this research were Jean-Jacques Rousseau, Carlos Coutinho, Wanderlei dos Santos, Dermeval Saviani, Luiz Cunha, Luiz Dourado and Jamil Cury.